DISTANCE LEARNING AS AN INNOVATIVE FORM OF POSTGRADUATE STUDIES IN HIGHER MEDICAL EDUCATION - Dubynska, G.M.; Kotelevska, T.M.; Iziumska, O.M.; Pryimenko, N.O.; Bodnar, V.A. (World of Medicine and Biology, 2017)
The article presents the experience of implementing distance technologies in postgraduate education of doctors at the Department of Infectious Diseases with Epidemiology of Higher State Educational Establishment of Ukraine «Ukrainian Medical Stomatological Academy», which promotes the continuous medical education, is one of the mechanisms for improving the quality of professional training and has economic efficiency. Under the conditions of intensive development of information technologies, further perspectives have been considered.
Keywords: distance learning; postgraduate training of doctors; information technologies; webinar; Infectious Diseases